Weak photoperiodic response facilitates the biological invasion of the harlequin ladybird Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae). (1st August 2014) - Reznik, S. Ya.; Dolgovskaya, M. Yu.; Ovchinnikov, A. N.; Belyakova, N. A.
Abstract Photoperiodic regulation of reproductive diapause in two invasive and two native populations of Harmonia axyridis and in one native population of Harmonia yedoensis was investigated in laboratory at 20°C, five photoperiods (day length of 10, 12, 14, 16 and 18 h) and two diets: (i) eggs of the Angoumois grain moth Sitotroga cerealella and (ii) the green peach aphid, Myzus persicae. Laboratory strains originated from native populations of H. axyridis from Irkutsk province of Siberia and H. yedoensis from South Korea showed a strong photoperiodic response: under short photoperiods (10–14 h and 10–12 h for H. axyridis and H. yedoensis, correspondingly), all females which fed on eggs and most of those fed on aphids did not start to lay eggs during 40 days after emergence, while under long photoperiods, all females fed on aphids and most of those fed on eggs oviposited. The photoperiodic response of H. axyridis from South Korea was less strong: on the both diets, the range of the photoperiodic response (the difference in the proportion of ovipositing females between the treatments with long and short days) was ca 40%. In the European (Czech Republic) and in the Caucasian (Sochi region, Russia) invasive populations of H. axyridis, the photoperiodic response was very weak: the proportion of females that started oviposition (when fed on aphids) or at least reproductive maturation (when fed on eggs) during 40 days after emergence was close to 100%, independently of the photoperiodic conditions. Obviously, instead of a rapid micro‐evolutionary adaptation of the critical day length to a new climate, the invasive populations of the harlequin ladybird decrease their dependence on photoperiod and thus the weak photoperiodic response of SE Asian population of H. axyridis can be considered as a pre‐adaptation further developed during the invasion.